Analisis Alih Kode dan Campur Kode pada Tututran Penjual dan Pembeli di Pasar Panimbang serta Pemanfaatannya sebagai Bahan Ajar Bahasa Indonesia di SMA - Sunia, Nia (Jurnal Artikula, 2025)
Analysis of Code Switching and Code Mixing in the Speech of Sellers and Buyers at Panimbang Market and Their Benefits as Indonesian Language Teaching Materials in High Schools". Indonesian and Regional Literature Language Education Study Program, Undergraduate Program (S1) Faculty of Teacher Training and Education, Mathla'ul Anwar University, Banten. This research aims to describe code switching and code mixing in the speech of sellers and buyers at Panimbang Market. The data source in this research is the speech of sellers and buyers, while the approach in this research is qualitative using descriptive. Data collection techniques include observation, recording techniques, data transcription, listening, analysis and then conclusions. Based on the research results obtained, types of code switching and code mixing were found in the speech of sellers and buyers at Panimbang Market. The use of code switching and code mixing can be used as teaching material in negotiation text material in grade ten